(untitled) (Research, Society and Development, 2023)
This study aimed to compare teenager´s eating habits from a public school in Glória de Goitá, county of the state of Pernambuco, who lived in urban and rural areas. A total of 232 adolescents, aged between 11 and 15 years old, participated in the study. A semi-quantitative questionnaire on food habits and frequency was applied. Regarding habits, it was observed that adolescents in urban areas consumed more added salt. Regarding the number of meals eaten per day, the result was similar between the two areas. Adolescents living in rural areas performed more exercises per week when compared to those living in urban areas. As for the frequency of food consumption, very similar values were observed in relation to the consumption of protein products, more frequently for protein of vegetable origin such as beans. Both fruits and vegetables were little consumed by adolescents in both areas of residence. The data found showed that eating habits in urban and rural areas were similar.